2011
DOI: 10.1128/jcm.01650-10
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Bacterial Communities Present in Lungs of Patients with Cystic Fibrosis from American and British Centers

Abstract: The aim of this study was to determine whether geographical differences impact the composition of bacterial communities present in the airways of cystic fibrosis (CF) patients attending CF centers in the United States or United Kingdom. Thirty-eight patients were matched on the basis of clinical parameters into 19 pairs comprised of one U.S. and one United Kingdom patient. Analysis was performed to determine what, if any, bacterial correlates could be identified. Two culture-independent strategies were used: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
48
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 38 publications
4
48
1
2
Order By: Relevance
“…In the CF centers in Denmark, an intensive antibiotic treatment strategy has been shown to prolong the life expectancy of the CF patients (10). In recent studies, the chronically infected lungs of CF patients have been observed to harbor multiple species (19,21). However, the strict antibiotic strategy employed in Denmark has led to only a small variety of microorganisms being found in the lungs of CF patients, compared to what is found in other studies (8,18,23).…”
contrasting
confidence: 39%
“…In the CF centers in Denmark, an intensive antibiotic treatment strategy has been shown to prolong the life expectancy of the CF patients (10). In recent studies, the chronically infected lungs of CF patients have been observed to harbor multiple species (19,21). However, the strict antibiotic strategy employed in Denmark has led to only a small variety of microorganisms being found in the lungs of CF patients, compared to what is found in other studies (8,18,23).…”
contrasting
confidence: 39%
“…Prior approaches to bacterial identification by DNA sequencing have included fluorescent Sanger sequencing of hundreds of small variable regions of 16S ribosomal amplimer clones (19,20), length heterogeneity (LH) PCR for 16S ribosomal variable regions (21), restriction fragment polymorphisms in 16S (19,21), arrays with bacterium-specific probes, such as PhyloChip (22,23), and early applications of NGS (24,25). These methods have been applied to various clinical situations, such as the microbiome of suboptimally controlled asthma (22), cystic fibrosis (19,21), chronic obstructive pulmonary disease (COPD) (24,26,27), bronchiectasis (28), pleurisy (20), forensic assessment of drowning (25), and intubated patients (23). These studies have revealed unexpectedly large numbers of bacterial genera in patients with clinical illnesses and in healthy individuals (29,30).…”
mentioning
confidence: 99%
“…En uno de los pocos estudios para evaluar las comparaciones geográficas, muestras de esputo de 19 pacientes con FQ en un centro en Reino Unido fueron comparados con las muestras obtenidas de 19 pacientes de un hospital de Estados Unidos (26) . Las diferencias en las especies entre los dos grupos mostraron diferencias significativas en la composición, abundancia y diversidad.…”
Section: Discussionunclassified
“…Por otro lado, la proteómica, basada en espectrometría de doble masa MALDI TOF/TOF (MS/MS), se está desarrollando rápidamente en investigaciones médicas, particularmente, comparando el proteoma de individuos sanos y enfermos (26) . En este estudio utilizamos esta técnica con el objetivo de obtener péptidos a partir de bacterias e identificar proteínas.…”
Section: Discussionunclassified